2018
DOI: 10.1136/esmoopen-2018-000428
|View full text |Cite
|
Sign up to set email alerts
|

Updated 5-year survival and exploratory T x N subset analyses of ACTS-CC trial: a randomised controlled trial of S-1 versus tegafur-uracil/leucovorin as adjuvant chemotherapy for stage III colon cancer

Abstract: ObjectiveAdjuvant Chemotherapy Trial of TS-1 for Colon Cancer (ACTS-CC), a randomised phase III trial, demonstrated that adjuvant therapy with S-1 for stage III colon cancer was non-inferior in 3-year disease-free survival (DFS) to that of tegafur-uracil plus leucovorin (UFT/LV). We updated DFS and overall survival (OS) and performed T x N subset analysisMethodsA total of 1518 patients with curatively resected stage III colon cancer were randomly assigned to receive S-1 (80–120  mg/day on days 1–28 every 42 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…One reported the completion rate was 51.4% (the rate for those without recurrence was not available) for BTC after major hepatectomy [13] and the other reported a complete rate of 75.8% (the rate for those without recurrence, 86.0%) [16]. Regarding other types of cancer, a 6-month administration of S-1 was completed in 76.5% of cases (rate for non-recurrence, not available) in colon cancer [20] and 72.2% (rate for those without recurrence, 75.8%) in pancreatic cancer [11]. Compared to other regimens for BTC, the BILCAP trial that evaluated a 6-month administration of capecitabine and the BCAT trial that evaluated a 6-month administration of gemcitabine showed the complete rates were 54.7 and 52.1%, respectively [9,21].…”
Section: Discussionmentioning
confidence: 99%
“…One reported the completion rate was 51.4% (the rate for those without recurrence was not available) for BTC after major hepatectomy [13] and the other reported a complete rate of 75.8% (the rate for those without recurrence, 86.0%) [16]. Regarding other types of cancer, a 6-month administration of S-1 was completed in 76.5% of cases (rate for non-recurrence, not available) in colon cancer [20] and 72.2% (rate for those without recurrence, 75.8%) in pancreatic cancer [11]. Compared to other regimens for BTC, the BILCAP trial that evaluated a 6-month administration of capecitabine and the BCAT trial that evaluated a 6-month administration of gemcitabine showed the complete rates were 54.7 and 52.1%, respectively [9,21].…”
Section: Discussionmentioning
confidence: 99%
“…One reported the completion rate was 51.4% (the rate for those without recurrence was not available) for BTC after major hepatectomy (13) and the other reported a complete rate of 75.8% (the rate for those without recurrence, 86.0%). (16) Regarding other types of cancer, a 6-month administration of S-1 was completed in 76.5% of cases (rate for non-recurrence, not available) in colon cancer (20) and 72.2% (rate for those without recurrence, 75.8%) in pancreatic cancer. (11) Compared to other regimens for BTC, the BILCAP trial that evaluated a 6-month administration of capecitabine and the BCAT trial that evaluated a 6-month administration of gemcitabine showed the complete rates were 54.7% and 52.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The intervals from PTM treatment to LT in the patients with advanced-stage colon cancer and breast cancer was 19 months and 9 years, and neither has experienced recurrence during the follow-up period. 5-year disease free survival rate in the patients with Stage IIIA colon cancer which was curatively resected and received chemotherapy was over 70% in the literature (31,32). We accepted the patient with advanced colon cancer as the candidate of transplant recipient.…”
Section: Discussionmentioning
confidence: 99%